2013
DOI: 10.1371/annotation/cdb46efb-fa7c-4507-93e9-eb739804ed8f
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Glucagon-Like Peptide-1(9-36) Inhibits Chemokine-Induced Migration of Human CD4-Positive Lymphocytes

Abstract: Introduction: Inhibitors of dipeptidyl peptidase-IV (DPP-IV), which decrease the degradation of glucose-lowering to the metabolically inactive , are current new treatment options for patients with type 2 diabetes mellitus, a high-risk population for cardiovascular disease. However, the effects of the metabolite GLP-1(9-36) on atherosclerosis are unknown. Thus, the present study examined the effect of GLP-1(9-36) on chemokine-induced CD4-positive lymphocyte migration as one of the early and critical steps in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…GLP-1 agonists have been increasingly used for the treatment of diabetes in clinical practice because of its insulinotropic beneficial effects against insulin resistance (2). The biological effects of GLP-1 are mediated by glucagon-like peptide-1 receptor (GLP-1R) (3), a seven-transmembrane G protein-coupled receptor family (4) that is expressed on many cell types, including macrophages (5)(6)(7)(8)(9). Translational and clinical studies have shown that GLP-1 and GLP-1R regulate glucose homeostasis and energy metabolism (10) and are involved in important physiological processes such as insulin release, b-cell proliferation, reduced glucagon release, delayed gastric emptying, and enhanced memory (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…GLP-1 agonists have been increasingly used for the treatment of diabetes in clinical practice because of its insulinotropic beneficial effects against insulin resistance (2). The biological effects of GLP-1 are mediated by glucagon-like peptide-1 receptor (GLP-1R) (3), a seven-transmembrane G protein-coupled receptor family (4) that is expressed on many cell types, including macrophages (5)(6)(7)(8)(9). Translational and clinical studies have shown that GLP-1 and GLP-1R regulate glucose homeostasis and energy metabolism (10) and are involved in important physiological processes such as insulin release, b-cell proliferation, reduced glucagon release, delayed gastric emptying, and enhanced memory (11,12).…”
Section: Introductionmentioning
confidence: 99%